2019
DOI: 10.22146/jmpf.37441
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Knowledge and Belief with Adult Patient’s Antibiotics Use Adherence

Abstract: The inappropriate use of antibiotics has resulted in bacterial resistance to antibiotics. One of the factors supporting this phenomenon is the lack of patient knowledge and belief of antibiotics. The study aimed to know the relationship between knowledge and belief with adherence in using antibiotics in adult patients at Syarifah Ambami Rato Ebu Hospital, Bangkalan, based on the Health Belief Model theory. This research is observational analysis using cross-sectional study. There were 103 patients chosen by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
1
2
0
6
Order By: Relevance
“…96 Antibiotic adherence levels were not associated with education level or employment status (2 studies). 98, 101…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…96 Antibiotic adherence levels were not associated with education level or employment status (2 studies). 98, 101…”
Section: Resultsmentioning
confidence: 99%
“…96 Antibiotic adherence levels were not associated with education level or employment status (2 studies). 98,101 Third, antibiotic dispensing without prescription was the most important theme reported among health care providers, with conflicting findings. A survey among 250 community pharmacists in Yogyakarta (Java), 68% reported that they would dispense antibiotics without prescription, 116 whereas a survey among 110 health providers in community health centres in Padang (Sumatera) found that 98.8% did not prescribe antibiotics without a prescription, despite patient request.…”
Section: Knowledge Attitudes and Perceptions On Antibiotic Use Among ...mentioning
confidence: 99%
“…antibiotik menjadi masalah utama perhatian dunia karena menyebabkan mortalitas, menurunkan efektifitas terapi. (Nuraini, et al, 2019). Saat menggunakan antibiotik, dianggap rasional jika tepat indikasi, dosis, interval, durasi, dan biaya semuanya dipertimbangkan.…”
unclassified
“…Antibiotik dapat digunakan secara bijak dan tepat untuk menurunkan tingkat resistensi. Kemanjuran terapi dan untuk mencegah munculnya resistensi, pemahaman masyarakat tentang obat antibiotik sangat penting (Nuraini, et al, 2019). Pemberian informasi farmakologi atau konseling pasien merupakan salah satu cara untuk meningkatkan kepatuhan pasien terhadap terapi.…”
unclassified
See 1 more Smart Citation